Treatment of otitis externa experimentally infected with Pseudomonas aeruginosa in dogs: Rana .A.M.Salih ;A.M.H.Judi - Salih, Rana .A.M. (The Iraqi Journal of Veterinary Medicine, 2009)
Twenty five local breed dogs divided to five groups and otitis extrna experimentally induced by scrashingthe ear canal with ( 9x10)8 cfu p6, biotype of pseudomonas aeruginosa . The control group showed theclinical signs beside the presence of neutrophils in the smears . The third group showed the clinical signsbeside the rupture of tympanic membrane in one of animal group and the recovery to the others in 4 weeksafter treathment withear washing acetic acid and boric acid and then local treatment with ciprofloxacin and dexamethazonebeside then local treatment with ciprofloxacin and dexamethazone beside we give ciprofloxacin orally . The fourth group recovered after 3 weeksof treatment with ear washing with Tris – EDTA beside acetic acid and boric acid and local treatment withciprofloxacin and dexamethazone beside giving cipro floxacin orally . The fifth group recoverd after4weeks of treatment with ear washing with Tris – EDTA and acetic acid and boric acid and local Treatmentonly with ciprofloxacin and dexamethazone